PENGEMBANGAN GAME EDUKASI SISKOM ADVENTURE PADA MATA PELAJARAN INFORMATIKA KELAS X DI SMK NEGERI 4 PADANG - Nadya Nadya; Adlia Alfiriani; Haris Kurniawan (Universitas Muhammadiyah Tapanuli Selatan, 2026)
Learning media plays an important role in improving the quality of the learning process. However, in Informatics subjects at SMK Negeri 4 Padang, the learning methods used are still conventional, resulting in low learning motivation and student learning outcomes. This study aims to develop the Siskom Adventure educational game as an interactive learning media and to test its validity and practicality levels for Computer Systems material for class X. This study uses the Research and Development (RD) method with the ADDIE development model consisting of the stages of Analysis, Design, Development, Implementation, and Evaluation. The resulting product is a platformer-based educational game that presents materials, challenges, and quizzes in game missions, so that students can learn through more interesting and interactive experiences. The results of the study show that validation by media experts obtained an average score of 85.06% (very valid), while validation by material experts reached 92.14% (very valid). The teacher's practicality test obtained a result of 83.33% (very practical), and the student's practicality test reached 88.34% (very practical). Thus, the Siskom Adventure educational game is deemed suitable for use as a learning medium capable of increasing student motivation, interactivity, and learning outcomes.